2018
DOI: 10.1103/physrevb.98.224203
|View full text |Cite
|
Sign up to set email alerts
|

Temperature rise in shear bands in a simulated metallic glass

Abstract: Temperature rise (∆T ) associated with shear-banding of metallic glasses is of great importance for their performance. However, experimental measurement of ∆T is difficult due to temporal and spatial localization of shear bands and, as a result, our understanding of the mechanism of ∆T is limited. Here, based on molecular dynamics simulations we observe a spectrum of ∆T , which depends on both sample size and strain rate, in the shear bands of CuZr metallic glass under tension. More importantly, we find that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…2(a)]. The slope of this linear part have weak dependence on the strain rate [51,52]. Note that the high elastic moduli will correspond to materials with more pronounced elasticity.…”
Section: Amorphous Niti Under Various Types Of Deformationmentioning
confidence: 99%
“…2(a)]. The slope of this linear part have weak dependence on the strain rate [51,52]. Note that the high elastic moduli will correspond to materials with more pronounced elasticity.…”
Section: Amorphous Niti Under Various Types Of Deformationmentioning
confidence: 99%
“…deformation, which generates a temperature change from 278 K to more than 1273 K [21]. According to the molecular dynamic simulation, an increase of temperature in the shear bands of CuZr metallic glass is correlated positively with the strain rate under tensile loading [22]. However, the molecular dynamic simulation results showed that the cutting temperature of Zr-50Cu30 metallic glasses can reach 600-700K in the nanoscale cutting process [23].…”
Section: Methodsmentioning
confidence: 99%
“…However, it is rather difficult to experimentally and accurately access heat generation and temperature inside the bulk of material (i.e, away from surfaces), and one is thus often restricted to apply indirect methods and rough estimates. Indeed, reported values of in the existing literature are distributed over a broad range, differing sometimes by several orders of magnitude [ 7 , 12 , 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%